Analysis of status and Socioeconomic of Female Agricultural workers in the Himachal Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The agricultural labour and the Indian economy rely heavily on women. The physical result is produced efficiently and with high quality by women who offer the work. A large portion of the agricultural labour consists of rural women, sometimes referred to as "agriculture women," who are essential to the industry. The data required by policymakers & government to raise agriculture women's economic & social status is provided. This investigation to examine agricultural women's status and socioeconomic contribution in the study area. The researcher will select the Himachal Pradesh districts of Kangra and Una at spontaneously. The present study makes use of both primary and secondary sources. Secondary data will acquire from sources including books, journals, reports, and records kept by the Agricultural Departments at the State, District, Division, and Block levels will use to analyze the current state of agriculture's workers. Secondary data will gather from relevant sources with the goals in mind. The researcher will conduct an extensive interview schedule to acquire primary data from the sample of 500 respondents.